Implementation of Benson Relaxation Therapy to Reduce Anxiety in Anxiety Patients in the Inpatient Room at Woodward Hospital, Palu : A Case Study - Emilia, Ni Luh; Herman, Fadila; Restawan, I Gede (PT.Mantaya Idea Batara, 2025)
Background: Anxiety is a common psychological condition often experienced byinpatients due to changes in health status, unfamiliar environments, anduncertainty about treatment. If left untreated, anxiety can lead to various negativeoutcomes, including increased blood pressure, sleep disturbances, and excessiverestlessness. One effective non-pharmacological intervention to reduce anxiety isBenson relaxation therapy, which combines deep breathing techniques with therepetition of calming words or prayers. This study aimed to apply Bensonrelaxation therapy to reduce patient anxiety in the inpatient ward of WoodwardHospital, Palu.Methods: A descriptive case study design with a nursing careapproach was employed. The subject of the study was one patient experiencingmoderate anxiety. Benson relaxation therapy was administered for four days,twice daily, with each session lasting 10–20 minutes. Anxiety levels weremeasured using the Hamilton Anxiety Rating Scale (HARS). Result: The HARSscore decreased from 25 (moderate anxiety) to 16 (mild anxiety). The patient alsoshowed improvements in sleep patterns, reduced muscle tension, and alleviationof somatic symptoms such as dizziness and restlessness. Conclusion: Bensonrelaxation therapy effectively reduces anxiety in hospitalized patients,contributing to the resolution of anxiety-related problems.